La tutela dell’ambiente nella dottrina sociale della Chiesa (Stato, Chiese e pluralismo confessionale, 2023)
Environmental protection in the Catholic social teachingABSTRACT: This short essay aims to analyse the evolution of the Catholic social teaching regarding environmental protection. Starting from a famous article by T. Lynn White in 1966, the Judaic-Christian doctrine on the men-nature relationship has been frequently qualified as a strongly anthropocentric one, being also considered as an ideological premise of men's exploitation of the environment and, as a consequence, of the actual ecological crisis. This contribution, moving from the analysis of the Catholic social teaching on environmental safeguard and of some relevant theological, historical and social issues, explains why this idea needs to be rejected and try to imagine which role the Catholic Church, and Christianity in general, can have in facing the environmental crisis in the future.SOMMARIO: 1. Introduzione - 2. Il rapporto uomo-ambiente nel contesto teologico contemporaneo - 3. Nascita e primo sviluppo del magistero pontificio in materia di tutela ambientale. - 4. Questione ambientale, interesse sociale e responsabilità morale - 5. Cultura, morale e rispetto dell’ambiente - 6. Le prospettive di una ecologia integrale - 7. Riflessioni conclusive.